1984
DOI: 10.1001/archotol.1984.00800280038011
|View full text |Cite
|
Sign up to set email alerts
|

Permucosal Needle Drainage of Peritonsillar Abscesses: A Five-Year Experience

Abstract: \s=b\ Forty-one patients with proved peritonsillar abscesses were treated during a five-year period with needle aspiration as the sole initial surgical treatment. Ninety percent (37/41) of the patients' abscesses resolved without further invasive therapy. All but two of the patients were treated as outpatients. Fifty percent (21/ 41) of the patients were treated by nonotolaryngologists. These data indicate that outpatient needle aspiration is the simplest, most cost-effective therapy for peritonsillar abscess.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0
1

Year Published

1984
1984
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 7 publications
0
27
0
1
Order By: Relevance
“…Both these methods have been demonstrated to be equally clinically effective. [6][7][8][9][10][11][12][13][14] There are, however, significant differences in the mode of treatment used according to the caseload managed, with departments treating more than 20 patients a year more likely to use aspiration. Moreover there appears to be geographical variations in the choice of mode of treatment, with significantly more surgeons in England and Wales using incision and drainage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both these methods have been demonstrated to be equally clinically effective. [6][7][8][9][10][11][12][13][14] There are, however, significant differences in the mode of treatment used according to the caseload managed, with departments treating more than 20 patients a year more likely to use aspiration. Moreover there appears to be geographical variations in the choice of mode of treatment, with significantly more surgeons in England and Wales using incision and drainage.…”
Section: Discussionmentioning
confidence: 99%
“…6 Moreover, there are several studies that have demonstrated the effectiveness of outpatient treatment. 9 14 15 This difference may be due to the differences in set-ups and outpatient support mechanisms of the health services in the two countries, or may be driven by economic factors. It, however, highlights an area that requires further study, and we are currently in the process of evaluating out patient treatment in the UK setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the last decades, the results of NA and ID were repeatedly reported, even their application in children [288]. The advantages of NA, introduced by King in 1961 [357], encompass: easy-to-learn, easy-to-perform, rapid confirmation of a clinical suspicion, minimal trauma, good tolerance, immediate relief, no surgical/anesthesiological risks, low pain intensity [301], [304], [305], [358]. However, some disadvantages have to be mentioned, such as: painful procedure, aspiration of leaking pus, potential risk of painful re-draining, and the risk of damaging the internal carotid artery [288].…”
Section: Resultsmentioning
confidence: 99%
“…Because of the moderate quality of the identified studies, only answers with recommendation grade C could be given for questions 2 and 3. Among those 42 publications, there were only 5 level I trials [263], [304], [345], [363], [364], the remainder were classified as level IV including 13 case series with only one treatment modality [301], [302], [303], [305], [314], [343], [358], [374], [375], [376], [377], [378], [379], 12 case series comparing different therapies [261], [264], [307], [308], [366], [380], [381], [382], [383], [384], [385], [386], and one economic analysis [301]. Concerning recurrence rates and indication, the authors found 2 level II studies [309], [313] and 13 level IV trials [301], [303], [310], [311], [312], [314], [343], [350], [361], [372], [387], [388], [389].…”
Section: Resultsmentioning
confidence: 99%